Opening up by writing it down : how expressive writing improves health and eases emotional pain - Pennebaker, James W.; Smyth, Joshua M. (New York : The Guilford Press, 2016)
"Expressing painful emotions is hard--yet it can actually improve our mental and physical health. Distinguished psychologist James W. Pennebaker has spent decades studying what happens when people take just a few minutes to write about deeply felt personal experiences or problems. This lucid, compassionate book has introduced tens of thousands of readers to an easy to use self help technique that has been proven to heal old emotional wounds, promote a sense of well being, decrease stress, improve relationships, and boost the immune system. Updated with findings from hundreds of new studies, the significantly revised second edition now contains practical exercises to help readers try out expressive writing. It features extensive new information on specific health benefits, as well as when the approach may not be helpful"--
Introduction -- 1. "Shh ... It's a Secret": Beginning to Explore the Connection between Confession and Health -- 2. The Invention of the Expressive Writing Approach -- 3. What's on Your Mind? Health Benefits of Verbal and Written Disclosure -- 4. Dealing with Chronic Health Problems Using Expressive Writing -- 5. Writing to Clear the Mind: Expressive Writing in Learning and Education -- 6. "Get These Thoughts Out of My Head!" Getting Past Obsessions, Insomnia, and Bouts of Stupidity -- 7. To Speed Up or Slow Down? How People Differ in Coping with Trauma -- 8. "I'm Here for You ... or Am I?" The Audience on the Other End of Our Words -- 9. How Does Writing Help Us Secure a Healthier and Happier Future? -- 10. Pulling It All Together: Recommendations for Your Use of Expressive Writing -- Notes -- Bibliography.
Revision of: Opening up / James W. Pennebaker. 1997.
Includes bibliographical references (pages 183-198) and index.
Keywords: Self-disclosure -- Health aspects; Written communication -- Therapeutic use; Stress (Psychology) -- Prevention; Mind and body